Морфологія та оптичні константи нанокристалічних плівок Gе на поверхні Sі(001) - Kozyrev, Y. N.; Lysenko, V. S.; Gomeniuk, Y. V.; Kondratenko, O. S.; Iliash, S. A.; Kondratenko, S. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2016)
The Ge and SiGe nanocrystalline films were grown on Si(001) surface by molecular-beam epitaxy. The optical constants of thin films were determined by multy-angle monochromatic ellipsometry. Optical properties of such systems were described using the Bruggeman's theory of effective medium approximation. Deposition of Si on the surface with Ge nanoclusters changes the effective optical constants due to porosity of the nanocrystalline films.